Pelatihan Pemanfaatan ID Author bagi Dosen - Havis Aravik; Ahmad Tohir (AKM, 2021)
Training activities for the use of Author ID for Lecturers in the STEI Al-Furqon Prabumulih environment can be carried out well and smoothly due to the collaboration of the Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang with STEI Al-Furqon Prabumulih which was held on April 6, 2021 in the STEI Hall Al-Furqon Prabumulih from 08.00 WIB to 16.30 WIB. The purpose of this activity is to provide understanding and knowledge about Author IDs that a lecturer must have in supporting the Tridharma of Higher Education which he must carry out every semester. This activity uses the method of material presentation, guidance and practice of making Author ID and evaluation. The result of this training is that Author ID is an important component that every lecturer must have in order to support the success of the Tridharma of Higher Education which is implemented. With the Author ID, each lecturer can improve scientific publications and disseminate knowledge quickly to the community and even the world.